Modern prescribing practices and perspectives among Indian Orthopaedicians on Denosumab in osteoporosis: a cross-sectional survey - Mahendra, S. K.; Mehta, Sucheta; Dhonde, Devika; Dhanasekaran, Krishna Shriram (International Journal of Research in Orthopaedics, 2025)
Background: Denosumab reduces vertebral, hip and nonvertebral fracture risk by improving bone mineral density (BMD) in Osteoporosis. This survey aimed to understand the prescribing patterns and perspectives of Denosumab Indian Orthopaedic practice. Methods: This cross-sectional survey was conducted among Indian Orthopaedicians for insights on Denosumab prescription patterns, patient profile, treatment duration, adherence, safety and efficacy. Data were analysed descriptively by cross-tabulation. Results: Among 91 Orthopaedicians prescribing Denosumab for Osteoporosis (T-score<-2.5), 63.74% prescribed for fragility fractures, 60.44% to prevent recurrent fractures and 57.14% in patients without fragility fractures. Denosumab was preferred considering better patient compliance (56.04%), safety (54.95%), efficacy (51.65%) and dosing frequency (49.45%). Patient adherence for up to three years was reported by 79.13%. Teriparatide was the most common drug prescribed in combination (55%) or sequential manner (60% pre and 30.43% post-denosumab). Calcium and Vitamin D were supplemented by 94.51% of doctors. Denosumab drug holiday was not recommended by 62.64%. Approximately 52.7% and 66.7% of doctors reported 10% and 20% BMD increases after 12 and 12-24 months of therapy, respectively. Highest improvements were reported in the lumbar spine and hip. Myalgia (60.44%) and musculoskeletal pain (26.37%) were the most common side effects. Among all, 82.4% prescribed Denosumab in elderly osteoporotic patients with co-morbidities like diabetes (85.33%), cardiovascular disorders (62.67%), renal (54.67%) and hepatic impairment (21.33%). Conclusions: Our findings underscore the significance of Denosumab in Osteoporosis with insights into the prescribing patterns of Indian Orthopaedicians. It highlights the need for strategies to improve patient adherence for optimizing therapeutic outcomes.